From images to physics-based computational models to digital twins: a framework for personalized cancer therapies - Moradi Kashkooli, Farshad; Zhan, Wenbo; Bhandari, Ajay; Yusufaly, Tahir I.; Kolios, Michael C.; Rahmim, Arman; Soltani, M. (Frontiers in Radiology, 2026)
In this work, we highlight recent advances in computational modeling that have significantly enhanced prospects of personalized cancer therapies by enabling insightful integration of patient-specific data, including medical images. Computational models, encompassing multi-physics and multi-scale approaches, can simulate drug transport and interactions within tissues and environments, including the tumor microenvironment, and facilitate the development of targeted diagnostic and therapeutic strategies. The incorporation of machine learning algorithms has further refined modeling, improving predictive accuracy and enabling real-time adaptive treatment planning. Although challenges remain in model validation and clinical translation, ongoing advancements are steadily bridging these gaps, bringing computational models and technologies closer to routine clinical application for the improvement of patient outcomes.